Beamforming Algorithm of LEO Satellite Communication System - Haiwang WANG; Chenguang HUANG; Cheng ZOU; Fengwei SHAO; Jiachao CHANG; Guotong LI (天地一体化信息网络)
The rapid development of broadband satellite internet has brought satellite communication into a new era.The establishment of large-scale low-orbit satellite constellations has gradually saturated spectrum resources, and the high overlap in frequency use has led to serious interference problems between satellite communication systems.Satellite payloads typically communicate using phased-array antennas, which reduce interference by beamforming at the receiving and transmitting ends.The adaptive beamforming algorithm was used at the receiving end to suppressed interference by adaptive zeroing; The low sidelobe beamforming algorithm was used at the transmitting end, which reduced the interference by imposing specifi c constraints on the sidelobes to suppressed the sidelobe level.Three anti-jamming beamforming algorithms were introduced for the ground receiving end and the satellite sending end respectively, which provided a beamlevel method for reduced the interference between satellite communication systems.